Science outreach and capacity building in geomagnetism and space sciences—An Indian Institute of Geomagnetism endeavor - Gawali, P.B.; Bhaskar, Ankush; Dhar, Ajay; Ramesh, D.S. (My University, 2016)
We present an overview of science outreach and capacity building activities at the Indian Institute of Geomagnetism (IIG) against the backdrop of a long history of geomagnetic studies. We also present the future plans of the institute for strengthening these activities.
Keywords: Science Outreach; Geomagnetism; Space sciences; Indian Institute of Geomagnetism; IIG; Geomagnetic studies